World no tobacco day, 31 May 2023: “we need food, not tobacco” a commitment to a smoke-free generation - Lohshini Kanoo, Lina; Ismail, Ilham Ameera (Faculty of Medicine, 2023)
Puncak Alam, 31st May, 2023 - Al-Sultan Abdullah Hospital (HASA) and the Faculty of Medicine (UiTM) focus on patient treatment and emphasize disease prevention. World No Tobacco Day (WNTD) is an initiative by the World Health Organization (WHO) since 1997 that serves as a global platform to raise awareness about tobacco-related issues, preventable deaths, and diseases.